The genome sequence of Erhard’s wall lizard, Podarcis erhardii (Bedriaga, 1882) [version 1; peer review: 2 approved] - Joana Meier; Nathalie Feiner; Tobias Uller; Panayiotis Pafilis; Kinsey M. Brock (Wellcome Open Research, 2025)
We present a genome assembly from a female specimen of Podarcis erhardii (Erhard's wall lizard; Chordata; Lepidosauria; Squamata; Lacertidae). The assembly contains two haplotypes with total lengths of 1,495.98 megabases and 1,477.75 megabases. Most of haplotype 1 (99.28%) is scaffolded into 20 chromosomal pseudomolecules, including the W and Z sex chromosomes. Haplotype 2 was assembled to scaffold level. The mitochondrial genome has also been assembled, with a length of 17.14 kilobases.